Method development for detection and removal of multi-class pharmaceutical residues in hospital wastewater / Husam I. S. Kafeenah - Husam I. S. , Kafeenah (2019)
Sensitive detection method is basic to detect and monitor pharmaceutical waste in an environment. Simultaneous determination of multi-classes pharmaceutical compounds with different chemical properties at trace level is desirable in obtaining reliable data within a short time and low cost with good accuracy. In the first part of this study, a new detection method was developed for multi-classes pharmaceuticals in tap water and wastewater samples using solid phase extraction based on disk for clean-up and pre-concentration, prior to the analysis by ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Ten types pharmaceuticals of different polarity and chemical properties (acetaminophen, caffeine, diclofenac, ibuprofen, mefenamic acid, metformin, nifedipine, perindopril, salbutamol and simvastatin) were studied. Therefore, electrospray ionisation (ESI) in positive and negative ionisation modes was employed simultaneously for the UPLC-MS/MS analysis of these acidic, neutral and basic pharmaceutical compounds. The feature of the current method was in using a disk solid phase extraction (SPE) for single pre-treatment of polar, semi-polar and nonpolar pharmaceutical analytes. The performance of disk solid phase extraction and cartridge solid phase extraction were compared. Disk SPE gave higher sensitivity and recovery and consumed less analysis time and solvent. The method validation shows good absolute recovery ranged from 70 % to 122 % of tap water, 62 % to 121 % for effluent wastewater and 62 % to 121 % for influent wastewater except for metformin, which the absolute recovery values were approximately 48 % for all sample types. The results indicated that the new developed method was successfully applied to all the targeted pharmaceuticals in three different matrices, including tap water, effluent, and influent wastewater. The method shows high sensitivity and good precision as compared to corresponding methods. Most of the targeted pharmaceuticals were detected in the influent and effluent wastewater obtained from hospital treatment plant at different concentrations. The result also showed a variation in the treatment efficiencies for the hospital treatment plant from one compound to another with the removed rate ranged from 0 % to 99 %. In the second part of this study, a new green approach for the removal of the multi-class pharmaceutical residues from the wastewater in a batch process using two different activated carbons (a homemade activated carbon prepared from Artocarpus integer fruit peels and commercial activated carbon) was investigated. The results obtained from the batch removal experiments proved that the method succeeded to eliminate all the targeted pharmaceutical residues from the effluents wastewater at high percentages of removal (95 %-100 %). An adsorption kinetic test showed rapid adsorption using both activated carbons for most of the pharmaceuticals within the first 20 min. The adsorption kinetic process of the two adsorbents for all the pharmaceuticals is categorized as a pseudo-second order.